Identifikasi Projek Penguatan Profil Pelajar Pancasila (P5) dalam Menguatkan Pendidikan Karakter Religius - Zulfa, Wafda; Partono, Partono (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2024)
This research aims to determine and describe the religious character of class VII students at SMP 1 Kudus, the implementation of the Project for Strengthening the Profile of Pancasila Students in class VII at SMP 1 Kudus, as well as strategies for strengthening religious character education through the implementation of the Project for Strengthening the Profile of Pancasila Students in class VII at SMP 1 Kudus. This research is a type of qualitative research with data collection methods using observation, interviews and documentation. The analysis technique in this research uses data triangulation. The results of the research show that the religious character of class VII students at SMP 1 Kudus can be seen from the indicators: (a) religious tolerance and the absence of bullying, (b) helping each other in difficulties, giving and loving, (c) carrying out habitual activities as support religion, namely midday prayers in congregation. The implementation of P5 at SMP 1 Kudus is going well in accordance with the guidelines for developing the project to strengthen the profile of Pancasila from the Ministry of Education and Culture. The strategy for strengthening religious character education through the implementation of P5 in class VII SMP 1 Kudus is derived from dimensions that are able to strengthen students' religious character; (a) mutual cooperation, (b) global diversity, and (c) devout faith and noble character.